2016
DOI: 10.1007/s12020-016-1158-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phthalates and bisphenol A on the obesity development and glucose metabolism disorders

Abstract: The prevalence of obesity and type 2 diabetes mellitus epidemics presents a great health problem worldwide. Beside the changes in diet and decreased physical activity, there is growing interest in endocrine disrupting chemicals that may have effects on these conditions. Among them, the role of certain phthalates and bisphenol A is confirmed. We have summarized the existing literature on this issue including cross-sectional, follow up epidemiological studies and in vivo and in vitro studies. Most data support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 125 publications
1
107
0
Order By: Relevance
“…Metabolic syndrome that is characterized by the coincidence of hypertension, dyslipidemia, abdominal obesity, and hyperglycemia, is a main predisposing factor of cardiovascular diseases. Diet, sedentary lifestyle as well as exposing to endocrine disturbing chemicals as the case bisphenol A (BPA) have been promoting impacts on the characteristic feature of the metabolic syndrome (Stojanoska, Milosevic, Milic, & Abenavoli, ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome that is characterized by the coincidence of hypertension, dyslipidemia, abdominal obesity, and hyperglycemia, is a main predisposing factor of cardiovascular diseases. Diet, sedentary lifestyle as well as exposing to endocrine disturbing chemicals as the case bisphenol A (BPA) have been promoting impacts on the characteristic feature of the metabolic syndrome (Stojanoska, Milosevic, Milic, & Abenavoli, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular targets have been identified to explain the obesogenic effect of BPA . Indeed, it has been reported that BPA, in concentration ranges of μ m , interacts with Nuclear Receptors (NR), Estrogen Receptors (ER), Glucocorticoid Receptors (GR), peroxisome proliferator‐activated receptor γ (PPARγ), the Retinoid X Receptor (RXR) and Thyroid Receptors (TR) .…”
Section: Obesogenic Activity Of Bisphenol Amentioning
confidence: 99%
“…Epidemiological studies Several recent reviews have been published concerning epidemiological data and the link between BPA exposure and obesity [39,[48][49][50][51].…”
Section: Impact Of Bpa In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, BPFL is used as a substitute of BPA in the production of “BPA‐free” plastics . The estrogenic activity of BPA and its substitutes are known to cause various reproductive and metabolic disorders such as obesity, type‐2 diabetes mellitus ,. However human exposure to BPFL and its effects is not yet clear.…”
Section: Introductionmentioning
confidence: 99%